Bolivia : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2003)
Bolivia's system to prevent and suppress money laundering fulfills most of the Financial Sanctions Related to Terrorism and Terrorist Financing (FATF) recommendations and applies to the insurance, stock market, and financial sectors. However, the system does not include other activities that are susceptible to money laundering. The institutional regulatory and financial intelligence responsibilities for combating money laundering are concentrated in the Bolivian Financial Intelligence Unit. Bolivia should continue to improve the legislation aimed at combating this offense, and strengthen the imposition and supervision of controls.